Development of Rental House Mobile Application - Ab Rahman, Siti Zulaikha; Ab.Aziz, Ruhaya (Applied Information Technology And Computer Science, 2022)
University students need either a college or a rented house as a place to live throughout their studies. Since UiTM Kota Bharu does not provide college for students, students need to find a house  to stay. Hence, a rental house search system using a mobile application is built to help the searching and making initial decision. The case study of this project is conducted at UiTM Kota Bharu. The development methodology of this project is a prototype model. The software IDE used is Android Studio, programming language used is Java and database used is Firebase. The System users are Non Resident Community Unit (NRC)  as administrator, student and homeowner as public users. This system consists of six modules which are registration and login module, advertisement module, search module, booking module, profile module and report module. With the development of this system, it will help students find a comfortable home.